2015
DOI: 10.1149/2.0741509jes
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sulfide Additives in Achieving Long Cycle Life Rechargeable Iron Electrodes in Alkaline Batteries

Abstract: Iron-based alkaline rechargeable batteries such as nickel-iron and iron-air batteries are promising candidates for large-scale energy storage applications because of their relatively low cost, inherent robustness to cycling, and eco-friendliness. In the present study, we demonstrate iron electrodes containing iron (II) sulfide and bismuth oxide additives that do not exhibit any noticeable capacity loss even after 1200 cycles at 100% depth of discharge in each cycle. In iron electrodes prepared with bismuth sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 41 publications
5
64
0
1
Order By: Relevance
“…Recently, Narayanan et al have reported that conductive phase of sparingly soluble iron (II) sulfide prevents rapid passivation of iron electrode during discharge and sulfide ions reduce overpotential for the conversion of magnetite to metallic iron. 13 The present study also reflects that sulfide ions from bismuth sulfide have bi-functional role both in charging and discharging reactions of iron electrodes. Beneficial effects of bismuth sulfide additives are that (a) it promotes the reduction of magnetite to iron and hence capacity of iron electrode is increased, (b) it stabilizes and facilitates precipitation of crystalline ferrous hydroxide, (c) it prevents the formation of magnetite during the first step of discharge reaction, and (d) it enhances the cycle life of iron electrodes.…”
supporting
confidence: 72%
“…Recently, Narayanan et al have reported that conductive phase of sparingly soluble iron (II) sulfide prevents rapid passivation of iron electrode during discharge and sulfide ions reduce overpotential for the conversion of magnetite to metallic iron. 13 The present study also reflects that sulfide ions from bismuth sulfide have bi-functional role both in charging and discharging reactions of iron electrodes. Beneficial effects of bismuth sulfide additives are that (a) it promotes the reduction of magnetite to iron and hence capacity of iron electrode is increased, (b) it stabilizes and facilitates precipitation of crystalline ferrous hydroxide, (c) it prevents the formation of magnetite during the first step of discharge reaction, and (d) it enhances the cycle life of iron electrodes.…”
supporting
confidence: 72%
“…4) and further recombination of these ions with iron hydroxide to form iron sulfide within the electrode structure. [38][39][40] The amount of iron sulfide formation is proportional to the availability of iron (II) hydroxide formed during the forward reaction. After ten cycles, there are three well-developed oxidation peaks (A 0 , observed at −0.966 V, A 1 at −0.70 V and A 2 at −0.44 V), which are related to the adsorption of hydroxide ion, 41 further oxidation of Fe to Fe(II) and Fe(II) to Fe(III) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The iron (II) sulfide is sparingly soluble in the electrolyte, allowing pressed plate electrodes to be discharged at rates as high as 3C, and sustained charge and discharge cycling for over 1000 cycles. 44,45 We found that a sintered electrode could also be prepared with iron (II) sulfide. The discharge rate capability of such a sintered electrode with iron (II) sulfide was found comparable to that of the pressed plate iron electrode containing iron sulfide.…”
Section: Resultsmentioning
confidence: 97%
“…17 Our recent efforts with a "pressed-plate" type iron electrode have led to remarkable advances in charging efficiency and rate capability, achieved through electrode re-design and re-formulation. 17,[43][44][45] Such "pressed-plate" electrodes were prepared by hot-pressing of a mixture of the carbonyl iron particles, sulfide-containing additives, a pore-forming additive and a polymeric binder. However, greater mechanical robustness is projected for a "sintered-type" iron electrode when compared to other types of electrodes.…”
mentioning
confidence: 99%
See 1 more Smart Citation